The role of red blood cell indices to identify iron deficiency in anemic pulmonary tuberculosis patient - Tri Ratnaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: iron deficiency anemia (IDA) is often associated with infectionlinflammation disease, such as pulmonary tuberculosis. The biochemical parameters tests of iron metabolism are expensive relatively and not always available in some health centers. Objective: The aim of this study was to know the role of red blood cell indices to identify iron deficiency on pulmonary tuberculosis patient with anemia using a sTfR-based biochemical classification of ACD and ACD with iron deficiency (COMB!). Methods: The patient population consisted of 68 consecutive anemic pulmonary tuberculosis patients at the Sardjito Hospital and Balai Pengobatan Penyakit Paru-Paru 0.1. Yogyakarta, Indonesia. Result: Of 68 subjects, 53 had anemia of chronic disease (ACD) and 15 had iron deficiency anemia (COMBI). It was founded a significant difference between ACD group and COMBI group. There were significant correlations between red blood cell indices and sTfR. The most valid parameter to diagnose 10 is MCHC < 31.55 g/dL (Sn= 67%, Sp= 75%), followed by MCV < 81.65 fL (Sn= 62%, Sp= 73%), MCH < 25.75 pg (Sn= 67%, Sp= 70%), and lastly ROW> 14.95 (Sn= 73%, 57%). The diagnostic performances of this parameter at levels commonly used: MCV < 76 fL (Sn= 13%, Sp= 85%), MCH < 27 pg (Sn= 100%, Sp= 45%), MCHC < 31g/dL (Sn= 13%, Sp= 85%), and RDW > 15 (Sn= 67%, 60%). Conclusion: The usage of red blood cell indices can help us to identify iron deficiency in anemic pulmonary tuberculosis patients. For practical reason, more convenience if we use the value that is widely accepted. However, the red blood cell indices cannot be used solely, but must be combined for a greater accuracy.